Determinan Pemilihan Metode Kontrasepsi Vasektomi Pada Pria di Wilayah Kerja Puskesmas Buhit Kecamatan Pangururan Kabupaten Samosir 2024 - Sihaloho , Lasmauli; Manurung, Kesaktian; Sipayung , Rosetty; Sinaga , Taruli Rohana; Hutajulu , Johansen (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Introduction: High population growth rates impact development, necessitating restrictive policies through Long-Term Contraceptive Method (LTCM) programs. Vasectomy, as one of the LTCMs, still has very low acceptance, as seen in Pangururan District, where participation is less than 1%. Objective: This study aimed to analyze the factors associated with the selection of vasectomy as a contraceptive method among men in the working area of Buhit Public Health Center, Pangururan District, Samosir Regency. Methods: This study used a cross-sectional design with a quantitative approach. The population consisted of men with fertile-age wives, with a sample of 73 individuals selected through simple random sampling. Data were collected using a validated and reliable questionnaire. Data analysis used the Chi-Square test and logistic regression. Results: Bivariate analysis results showed significant relationships between the husband’s age (p = 0.039), number of children (p = 0.019), husband’s knowledge level (p = 0.047), attitude (p = 0.029), social norms (p = 0.016), and wife’s support (p = 0.001) with the decision to undergo vasectomy. Multivariate analysis proved that wife’s support was the most dominant variable (p=0.003; OR=23.500), meaning that husbands who received wife’s support were 23.5 times more likely to choose vasectomy. Conclusion: Wife’s support is the most dominant factor influencing the selection of vasectomy. Therefore, healthcare workers are expected to enhance their role through health education about vasectomy to the community, especially wives, to provide good support for their husbands.